Effective Viscosity in the Intracluster Medium During Magnetic Field Amplification via Turbulent Dynamo - S. Adduci Faria; R. Santos-Lima; E. M. de Gouveia Dal Pino (The Astrophysical Journal)
Galaxy clusters, the largest gravitationally bound structures, host a hot, diffuse plasma with poorly understood viscosity and magnetic field amplification. Astrophysical plasmas are often modeled with magnetohydrodynamics (MHD), but low collision rates in environments such as the intracluster medium (ICM) hinder thermodynamic equilibrium, causing pressure anisotropies and high viscosity. High- β plasmas, dominated by thermal pressure, are prone to instabilities (e.g., firehose or mirror) that limit anisotropy, reduce viscosity, and enable small-scale dynamo-driven magnetic amplification. This study examines viscosity evolution in the ICM during turbulent magnetic field amplification. We performed 3D MHD simulations of forced turbulence with an initially weak, uniform magnetic field. Using the Chew–Goldberger–Low (CGL)-MHD framework, we incorporate anisotropic pressure dynamics and instability-driven anisotropy limitation. We analyze effective viscosity and dynamo evolution, comparing results with Braginskii-MHD and uniform-viscosity MHD. Our results show that viscosity decreases over time, allowing magnetic field amplification to saturation levels similar to nonviscous MHD. Viscosity distribution becomes bimodal, reflecting (i) collisional values and (ii) turbulence-dominated values proportional to 1 × 10 ^−4 L _turb U _turb in unstable regions. At saturation, 60% of plasma retains collisional viscosity. Braginskii-MHD reproduces similar magnetic amplification and viscosity structures. However, uniform-viscosity MHD, where viscosity equals the mean saturated CGL-MHD value, fails to capture the turbulence inertial range. These findings highlight the need for anisotropic viscosity models in studying ICM processes such as magnetic topology, cosmic ray transport, and active galactic nucleus-driven shocks. Moreover, our CGL-MHD and Braginskii-MHD models match the Coma cluster density fluctuation spectrum, reinforcing its weakly collisional nature.